Evaluation of plant landscape at east Zijingang area of Zhejiang University based on analytic hierarchy process - ZHU Yunchen; MAO Yiping (浙江大学学报. 农业与生命科学版)
It has been several years since the promotion and application of analytic hierarchy process (AHP). Many scholars have used this model to analyze the configurations of plant landscape, but there are few using the quantitative and qualitative evaluation model of AHP to analyze high-class universities. One of the reasons is that these universities have large scale constructions, diversified plants, elaborated function blocks, and there are huge amount of statistics.East area of Zijingang campus, Zhejiang University was taken as an example. This area was divided into A, B, C three large plots and 10 blocks named by its original name. Based on AHP, the quantitative indicators were selected such as diversity of species, ornamental characteristics, and structure of life style at the three sample plots, and the qualitative indicators such as harmony of campus plants with whole habitat and hard landscape were screened by using the methods of questionnaire survey and examination on the spot.The results showed that the east area of Zijingang campus had rich vegetation and plant species diversity. It had achieved harmonious standards at plant landscape and architectural landscape, but its local plant landscape needed to be improved. Compared with A and B plots, plot C got the highest total score in the micro-level.In sum, the research provides a reference for plant landscape construction of other universities and lays a basis for plant landscape reconstruction on Zijingang campus of Zhejiang University.